An international study on implementation and facilitators and barriers for parent‐infant closeness in neonatal units. Issue 3 (13th August 2022) - van Veenendaal, Nicole R.; Labrie, Nanon H.M.; Mader, Silke; van Kempen, Anne A. M. W.; van der Schoor, Sophie R. D.; van Goudoever, Johannes B.; ,
ABSTRACT: Importance: Parent‐infant closeness and active parent participation in neonatal care are important for parent and infant health. Objective: To give an overview of current neonatal settings and gain an in‐depth understanding of facilitators and barriers to parent‐infant closeness, zero‐separation, in 19 countries. Methods: Neonatal intensive care unit (NICU) professionals, representing 45 NICUs from a range of geographic regions in Europe and Canada, were purposefully selected and interviewed June–December 2018. Thematic analysis was conducted to identify, analyze and report patterns (themes) for parent‐infant closeness across the entire series of interviews. Results: Parent‐infant separation during infant and/or maternity care is very common (42/45 units, 93%), despite the implementation of family integrated care (FICare) practices, including parent participation in medical rounds (17/45, 38%), structured education sessions for parents (16/45, 36%) and structured training for healthcare professionals (22/45, 49%). NICU professionals encountered four main themes with facilitators and barriers for parent‐infant closeness on and between the hospital, unit, staff, and family level: Culture (jointly held characteristics, values, thinking and behaviors about parental presence and participation in the unit), Collaboration (the act of working together between and within different levels), Capacities (resources and policies), and Coaching (education to acquire and transfer knowledge and skills). Interpretation: Implementing parent‐infant closeness in the NICU is still challenging for healthcare professionals. Further optimization in neonatal care towards zero‐separation and parent‐infant closeness can be achieved by enforcing the 'four Cs for Closeness': Culture, Collaboration, Capacities, and Coaching . Abstract : Implementing parent‐infant closeness in the neonatal intensive care unit is still challenging for healthcare professionals. Further optimization in neonatal care towards zero‐separation and parent‐infant closeness can be achieved by enforcing the 'four Cs for Closeness': Culture, Collaboration, Capacities, and Coaching .